Comparative Antibacterial Effects of Raw Extracts and Essential Oils of Ocimum gratissimum L. against Ralstonia solanacearum (Smith) - Wagura, A. G.; Kimeju, J. W.; Gichimu, Bernard M. (Knowledge Review, 2011)
Raw and processed products of Ocimum gratissimum reportedly contain some antibacterial effects. In this study, raw plant extracts and essential oils derived from leaves of Ocimum gratissimum were screened for their antibacterial properties on Ralstonia solanacearum, the causal agent of bacterial wilt in Irish potato at varying concentrations. The raw extracts were obtained through sequential cold extraction using methanol solvent while the essential oils were extracted through steam distillation. The test products were used at concentrations of 0.4, 0.2, 0.1, 0.05 and 0.025 mg mL_1. Antibacterial tests were done using paper disc diffusion inhibition method and antibacterial activity was determined by measuring the size of inhibition zones. The results showed that the five different concentrations of essential oils and plant extracts exhibited highly significant (p<0.0001) differences on their effects against growth of R. solanacearum. The study confirmed the antibacterial effects of O. gratissimum and further demonstrated that the active compound (s) against Ralstonia solanacearum is (are) concentrated in the essential oils.
Keywords: Ocimum gratissimum, Ralstonia solanacearum, essential oils, raw extracts, antibacterial effect